Erinnerung schreibt Geschichte Lateinamerika und Europa im Kontext transnationaler Verflechtungen - Luther, Inga; Elsemann, Nina; Bindernagel, Franka; Rinke, Stefan (Historamericana, 2022)
The anthology relates the Latin American continent to Europe. The contributions deal both with transnational dimensions of memory cultures and historical constructions and with the contradictions and conflict dynamics in connection with national historical discourses.